Comparison of the Use of Kinetic Model Plots and DD Solver Software to Evaluate the Drug Release from Griseofulvin Tablets - Ekenna, Ifeoma Cynthia; Abali, Sunday Okorie (Journal of Drug Delivery and Therapeutics, 2022)
Awareness of the release kinetics of active drugs is important in formulating drugs that have the desired delivery and in predicting the behaviour of the formulated drug in vivo. The study aims to determine the mechanism of drug release from griseofulvin tablets formulated with different surfactants using mathematical models and to compare the use of graphs and DD solver software in fitting dissolution profiles to kinetic models. The batches P1 -P3 were composed of the surfactant - PEG 4000 in different concentrations. A control batch without surfactant and a commercial brand (Mycoxyl 500) were used for comparison. Granule and tablet quality tests indicated quality formulations. Dissolution profiles showed that the surfactant improved drug release of griseofulvin and batches (batches P1 -P3) formulated with PEG 4000 had the best release profiles comparable with the commercial brand. The Excel Add-in DD solver and kinetic plots were used to determine the kinetic model of best fit. The Higuchi model was the best fit for batches P1 -P3. The first order and Hixon -Crowell also fit batches P2 and P3. The Korsmeyer’s model showed that batches P1 -P3 exhibited anomalous diffusion. The tablets formulated with PEG were as good as the commercial brand and they had an anomalous diffusion of the drug from the tablet; meaning that drug diffused following Fickian law and also diffused through a swollen and porous matrix. Kinetic plots and the DD solver can be used for fitting dissolution profiles to kinetic models. Keywords: Griseofulvin, Kinetics, Models, Surfactants, Polyethylene glycol (PEG) 4000, DD solver, Dissolution profile, mathematical models